Komunikasi Pemasaran Digital sebagai Tantangan Teknologi - Yulia Sari; Nadia Wasta Utami (Program Studi Ilmu Komunikasi UII, 2021)
The rise of internet users directly influences the usage of e-commerce platform in Indonesia. This growth also influences the competition between brands whom utilize e- commerce platform, hence companies need to address digital marketing communication as primary tools to compete in consumer market. As one of the most well-known shoes brand in Indonesia, Amazara fully realizes the potential of digital marketing sector and trying to implement digital marketing communication as one of its primary marketing strategy. This research examines the chosen communication strategy of Amazara in digital and internet platform. Primary data was taken from in-depth interview with owner and employees. Collected data was classified into categories and processed through data implementation to understand the depth knowledge about this specific case. Interpretation results were compared with theoretical context from literature studies, and formulated to reach primary conclusion. The results of the study indicate that the company has carried out planning and evaluation to develop digital marketing. The company has also developed an AIDA-based digital marketing strategy